Learning dan Coaching: Analisis Anteseden Manajemen Kinerja Dosen - Gusli Chidir; Dwi Ferdiyatmoko Cahya Kumoro; Muhammad Johan; Masduki Asbari; Dewiana Novitasari (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study investigates whether increased attention paid to coaching practice affects performance, while considering the mediating effect of learning capability. Data were collected from 61 lecturers of a private university in Jakarta using quantitative methods and confirmatory surveys. This study shows that coaching has a positive and significant impact on lecturer performance, either directly or indirectly through mediation of learning capability. The results of this study can have significant implications for HR managerial decision-making regarding the process of implementing new tools and training in university lecturers. This study also helps university HR management to seriously assess HR development investment plans in the form of coaching practices and direct their campus HR strategic planning.